Analysis of the Evidence Underpinning the American Academy of Orthopedic Surgeons Knee Osteoarthritis Clinical Practice Guidelines. (January 2023) - Waters, Philo; Anderson, Reece; Anderson, J. Michael; Scott, Jared; Detweiler, Byron; Streck, Sam; Hartwell, Micah; Torgerson, Trevor; Vassar, Matt
Context: Clinical practice guidelines (CPGs) are vital to establishing a standardized and evidence-based approach in medicine. These guidelines rely on the use of methodologically sound clinical trials, and the subsequent reporting of their methodology. Objective: To evaluate the completeness of randomized controlled trials (RCTs) underpinning CPGs published by the American Academy of Orthopedic Surgeons (AAOS) for management of osteoarthritis of the knee. Data Sources: We searched the most recent AAOS CPGs for surgical and nonsurgical management of osteoarthritis of the knee for RCTs. To estimate the necessary sample size, we performed a power analysis using OpenEpi 3.0 (openepi.com ). Study Selection: Two authors independently screened the reference sections of the included CPGs. Included studies met the definition of an RCT, were retrievable in the English language, and were cited in at least one of the included CPGs. Study Design: Meta-Analysis Level of Evidence: Level 1a Data Extraction: We performed double-blind screening and extraction of RCTs included in the AAOS CPGs. We evaluated each RCT for adherence to the Consolidated Standards of Reporting Trials (CONSORT) 2010 checklist. A multiple regression analysis was conducted to assess CONSORT adherence against characteristics of included studies (ie, type of intervention, funding source, etc). Results: Our study included 179 RCTs. The overall adherence was 68.5% with significant differences between those published before and since the development of the 2010 CONSORT guidelines ( P = 0.02). We found that RCTs receiving funding from industry/private sources as well as studies that included a conflict of interest statement showed more completeness than RCTs that reported receiving no funding ( P < 0.01). Conclusion: We found suboptimal CONSORT adherence for RCTs cited in AAOS CGPs for management of osteoarthritis of the knee. Therefore, the CPGs are likely supported by outdated evidence and lack of high-quality reporting. It is important that evidence used to guide clinical decision making be of the highest quality in order to optimize patient outcomes. In order for clinicians to confer the greatest benefits to their patients, CPGs should provide the totality of evidence and emphasize emerging high-quality RCTs to ensure up-to-date, evidence-based clinical decision-making.